Non-autonomous invariant sets and attractors: Random dynamical system - Mohamedsh Imran; Ihsan Jabbar Kadhim (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper the concepts of pullback attractor ,pullback absorbing family in (deterministic) dynamical system are defined in (random) dynamical systems. Also some main result such as (existence) of pullback attractors ,upper semi-continuous of pullback attractors and uniform and global attractors are proved in random dynamical system .